Role of Percutaneous Computed Tomography-guided Lung Biopsy in Non-resolving Consolidation and Identification of Clinical and High-resolution Computed Tomography Characteristics Predicting Outcome - Nath, Alok (J Clin Imaging Sci, 2019)
OBJECTIVE: Non-resolving consolidation (NRC) with inconclusive sputum, bronchoscopy, and bronchoalveolar lavage results poses a diagnostic dilemma. This retrospective analytical study was conducted to evaluate diagnostic yield and complications of percutaneous computed tomography (CT)-guided lung biopsy (PCLB) in NRC. Assessment of clinical features and high-resolution CT (HRCT) characteristics was also done which may predict outcome. MATERIALS AND METHODS: Data of PCLB performed for lung consolidation from January 2010 to January 2019 were retrospectively evaluated. For the determination of diagnostic yield, a positive result from any one specimen obtained by PCLB (tissue core, aspiration cytology, or microbiology) was sufficient to considered procedure diagnostic if it was concordant with clinical features, imaging findings, response to treatment, and subsequent follow-up. Student’s t-test and Fisher’s exact test were used for statistical analysis. RESULTS: Out of total 56 patients, final diagnosis was achieved in 48 (19 malignant and 29 benign). Diagnostic yield was 69.6%. Complications were noted in 10 patients including mild hemoptysis and pneumothorax, which were managed conservatively. No clinical feature was having statistically significant association with final diagnosis. HRCT findings significantly associated with malignant outcome were larger size of consolidation, multiple contiguous lobe involvement, multiple air-filled cysts inside consolidation, and associated ground-glass areas or multiple ground-glass nodules. The absence of air bronchogram was more common in benign cases. CONCLUSION: PCLB is a safe and useful method for obtaining specimen in NRC. Differentiation of benign from malignant outcome is not possible based on clinical findings; however, certain HRCT findings raise suspicion of malignancy.